2015
DOI: 10.1097/brs.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Symptoms and Function in Older Adults With Low Back Disorders

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 19 publications
8
66
4
2
Order By: Relevance
“…Notably, although nearly two-thirds of this sample experienced clinically meaningful reductions in pain intensity over 12 months, a substantial minority of veterans did not experience reductions in pain intensity and, in some cases, some experienced pain exacerbations. Indeed, some recent studies have shown that groups of patients with differing pain outcome trajectories can be identified and characterized 19, 23, 40 . Study findings call for further development of strategies that identify and target older individuals who have, or are more likely to have, treatment-refractory chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although nearly two-thirds of this sample experienced clinically meaningful reductions in pain intensity over 12 months, a substantial minority of veterans did not experience reductions in pain intensity and, in some cases, some experienced pain exacerbations. Indeed, some recent studies have shown that groups of patients with differing pain outcome trajectories can be identified and characterized 19, 23, 40 . Study findings call for further development of strategies that identify and target older individuals who have, or are more likely to have, treatment-refractory chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have methodologic differences, they have identified common trajectories of persistent, recovery, and developing back pain . Some of these studies have examined factors associated with the back pain trajectories identified ; however, none have compared health‐related outcomes in the back pain trajectory groups identified in the current study. Whether the patterns of back pain over time observed in the clinical samples of prior studies are also seen in the general population remains to be examined.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have examined the trajectories of back pain . The majority of these involved patients who presented to primary care settings with back pain , had a restricted age range , and/or had short follow‐up times (≤1 year) . Only a few studies have examined back pain in the general population using a wide age range .…”
Section: Introductionmentioning
confidence: 99%
“…Such new information could potentially help with the important efforts of identifying subpopulations of LBP patients who respond best to various types of treatments. 57,58 …”
Section: Limitations and Future Researchmentioning
confidence: 99%